THE IMPORTANCE OF EDUCATION AND THE ENVIRONMENT IN THE PREVENTION OF JUVENILE DELINQUENCY - Anggraini, Welly; Angelica, Destia; Bima, Hafiz Arya; Terangginas, Luxy; Ahmad, Syukron (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2024)
This research was carried out in Durian Village, Padang Cermin District, Pesawaran Regency. The focus of the study was to identify the factors contributing to juvenile delinquency. Juvenile delinquency refers to the violation of rules or laws by teenagers. The behavior exhibited can range from minor offenses like skipping school or breaking school rules, to more serious offenses such as vandalism, gang fights, and drug use. The author utilized the Qualitative Descriptive method, which involves describing the phenomena observed in the field based on the actual conditions and using problem-solving procedures that are appropriate for these conditions. The Accidental Sampling technique was used to select samples based on certain considerations that were expected to provide the most comprehensive data. The findings of this study revealed that the predominant type of juvenile delinquency in Durian Village was the use of cannabis-type drugs. The lack of parental supervision and attention, as well as the absence of religious and moral values in the children's environment, were identified as the primary causes of juvenile delinquency. Teenagers resort to drug use due to the influence of their environment and peers who engage in deviant behavior, while having limited understanding of the dangers associated with drugs. The families of adolescent drug users in Durian Village were found to be unable to provide the necessary attention, affection, and care to their children, leading the adolescents to behave as they pleased without anyone taking an interest in their actions.